The Foreign Policy of President Donald Trump and its impact on Latin America - Novak, Fabián (2018)
In this regard, the Institute of International Studies (IDEI) of the Pontifical Catholic University of Peru, supported by the Konrad Adenauer Foundation (KAS), considered it important to develop a research project that would precisely analyze the characteristics of President Trump’s foreign policy, establish its similarities and differences with the policies executed by other US presidents, and measure the impact that this policy has been having in different parts of the world, particularly in Latin America and the Caribbean. To do so, the authors decided to divide the work into four parts. The first is intended to review the foreign policy of the United States of America towards Latin America and the Caribbean between 1826 and 2016, in order to establish the different features or permanent guidelines of this policy towards the region. The second analyzes President Donald Trump’s foreign policy guidelines in relation to Europe, Asia and the Middle East, while the third part exclusively deals with the features of this policy towards the Latin American and Caribbean region. In this sense, Trump’s policy is studied in its commercial, migratory, environmental, democracy, cooperation, and other aspects. Finally, based on the information analyzed in the three previous chapters, the fourth part of this work develops the general and distinctive characteristics of foreign policy that President Trump has executed during the first 20 months of his term, that is, from January 2017 to September 2018. Preparing this work has required wide reading of literature related not only to the history of American foreign policy but also to the current policy executed by president Trump; hence not only scholarly sources but also journalistic sources have been used for the latter period. It should be noted that the analysis carried out in this work is based on foreign policy actions executed by President Trump and not on statements or proposals that have not been materialized. This is done with the purpose of being objective and truthful and not falling into the field of speculation. Definitely, a limitation for the drafting of this book was the fact that President Trump is halfway in his administration term. However, we also believe that sufficient time has elapsed and numerous important foreign policy actions have been carried out that allow drawing significant conclusions.